Multi-Scale Geophysical Methodologies Applied to Image Archaeological Ruins at Various Depths in Highly Terraneous Sites - Amin Ibrahim; Khaled S. Gemail; Kamal Abdelrahman; Naif Al-Otaibi; Elkhedr Ibrahim; Saada A. Saada (Remote Sensing, 2021)
Among all geophysical techniques, electrical resistivity and magnetic surveying as an integrative approach has been used widely for archaeological prospection at different scales of investigations. In this study, DC resistivity (1D vertical sounding and/2D/3D ERT) and magnetic surveys (total and gradient) as a multi-scale approach was applied in a highly terraneous archaeological site (Tell) with a case study to characterize and image the various archaeological assets at different depths with different spatial resolutions. Four critical zones of great interest within the considered Tell were surveyed. At the heart of the study area, three layers were depicted clearly from 1D resistivity sounding. A thick conductive zone of mostly clay is sandwiched between two resistive layers. The topmost layer contains construction debris (dated back to the Islamic Era), whereas the deeper layer could be related to Gezira sand on which the probable Pharaonic temple was constructed. A long 2D ERT profile using Wenner Beta (WB) and Dipole–Dipole (DD) arrays with a 5-m electrode spacing identified shallow high resistivity anomalies that could be related to construction ruins from fired bricks. Additionally, it succeeded in imaging the turtleback-shaped deeper resistive layer of mostly sand. At an elevated rim to the east and west of the Tell, total and vertical magnetic gradient maps clearly delineated different archaeological structures: the walls of the rooms of ancient Islamic settlers and the walls of water tanks from the Byzantine Era. Magnetic modeling assuming 2.5-dimensional magnetic models constrained by the 2D ERT inversion models could be used to create a realistic representation of the buried structures. Toward the northern part of the Tell, the joint application of the quasi-3D ERT inversion scheme and the magnetic survey revealed an anomaly of a well-defined geometric shape of an archaeological interest thought to be a crypt or water cistern based on nearby archaeological evidence. The overall results of the geophysical survey integrated with the image of some partially excavated parts provided the archaeologists with a comprehensive and realistic view of the subsurface antiquities at the study area.